Alquran Dan Konservasi Lingkungan (Suatu Pendekatan Maqashid al-Shari'ah) - Mamluatun Nafisah (Institut Agama Islam Negeri (IAIN) Curup, 2018)
The environment has been understood as a removable thing, thus draining the Excessive against nature for the sake of economy and technology, is considered a humane. This view is becoming disastrous to the natural events that until now difficult to overcome. This research aims to determine the Quran in depth perspective about environmental conservation with the approach ofThe environment has been understood as a removable thing, thus draining the Excessive against nature for the sake of economy and technology, is considered a humane. This view is becoming disastrous to the natural events that until now difficult to overcome. This research aims to determine the Quran in depth perspective about environmental conservation with the approach of maqashid al-syari'ah. This approach is used in order to determine the extent to which technical and operational utilization of the earth and the extent to which content is said to be exaggerated, with more emphasis on welfare. Findings of the research that the Quran outlines the basic values and practical substantive law in its management, including the principle underlying the utilization potential of the earth and the principle of maintenance. In order to take advantage of the potential of the earth, the Quran commands people to do the imarat al-ardh, that made the earth or the environment as a medium to realize the benefit of overall living creatures on earth. While the principle of its maintenance, the Quran emphasizes the importance of treating the environment well. One of the principles underlying the relationship between humans and nature are all beings have legal status muhtaram. maqashid al-syari'ah. This approach is used in order to determine the extent to which technical and operational utilization of the earth and the extent to which content is said to be exaggerated, with more emphasis on welfare. Findings of the research that the Quran outlines the basic values and practical substantive law in its management, including the principle underlying the utilization potential of the earth and the principle of maintenance. In order to take advantage of the potential of the earth, the Quran commands people to do the imarat al-aradh, that made the earth or the environment as a medium to realize the benefit of overall living creatures on earth. While the principle of its maintenance, the Quran emphasizes the importance of treating the environment well. One of the principles underlying the relationship between humans and nature are all beings have legal status muhtaram.